2017
DOI: 10.1002/2017gl073361
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the lower thermospheric winter‐to‐summer residual circulation on thermospheric composition

Abstract: Gravity wave forcing near the mesopause drives a summer‐to‐winter residual circulation in the mesosphere and a reversed, lower thermospheric winter‐to‐summer residual circulation. We conducted modeling studies to investigate how this lower thermospheric residual circulation impacts thermospheric composition (O/N2). We found that the upwelling associated with the residual circulation significantly decreases O/N2 in winter and the downwelling in summer slightly increases O/N2. Consequently, the residual circulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 27 publications
3
47
2
Order By: Relevance
“…In winter months the simulated meridional wind is the winter‐to‐summer lower thermospheric circulation that is above the summer‐to‐winter mesospheric circulation, driven by the dissipation of upward propagating gravity waves/tides (e.g., Holton, ; Lindzen, ; H.‐L. Liu, ; Qian, Burns, & Yue, ; Qian & Yue, ; Smith et al, ). This winter‐to‐summer wind is evident in Figure c, showing as the negative meridional wind above the summer‐to‐winter positive meridional wind in the Northern Hemisphere (winter hemisphere).…”
Section: Resultsmentioning
confidence: 99%
“…In winter months the simulated meridional wind is the winter‐to‐summer lower thermospheric circulation that is above the summer‐to‐winter mesospheric circulation, driven by the dissipation of upward propagating gravity waves/tides (e.g., Holton, ; Lindzen, ; H.‐L. Liu, ; Qian, Burns, & Yue, ; Qian & Yue, ; Smith et al, ). This winter‐to‐summer wind is evident in Figure c, showing as the negative meridional wind above the summer‐to‐winter positive meridional wind in the Northern Hemisphere (winter hemisphere).…”
Section: Resultsmentioning
confidence: 99%
“…This is done while keeping other species' number densities, temperature, and winds constant at the model lower boundary. This is different from Qian and Yue (2017) because our goal is to explain the mechanisms that are involved in lower‐upper thermospheric coupling in the context of lower thermospheric O concentration rather than the winter‐to‐summer circulation.…”
Section: Introductionmentioning
confidence: 87%
“…In the mesosphere, the meridional circulation is in the same direction, from summer to winter, but driven by a different mechanism. Large westward gravity wave drag in the winter hemisphere, and eastward gravity wave drag in the summer hemisphere causes the circulation to be from summer to winter through Coriolis force (Qian & Yue, 2017). Smith et al (2010) used O mixing ratio at 0.0046 hPa (84 km) from the Sounding of the Atmosphere using Broadband Emission Radiometry (SABER) instrument to show that there is a winter maximum in O which is likely linked to the abovementioned gravity wave driven downwelling in the winter.…”
Section: Introductionmentioning
confidence: 99%
“…Other mechanisms, including magnetospheric energy input (Walterscheid, ) and seasonal variations in gravity wave breaking and eddy diffusion (Qian et al, , ), were either found to be too weak or sufficient but not necessary conditions for driving the global AO and SAO in the ionosphere and thermosphere. Qian and Yue () found that the lower thermospheric residual circulation can impact the latitudinal gradient of thermosphere composition and thus can influence the thermospheric AO and SAO. In order to fully understand thermospheric AO and SAO, and the corresponding mechanisms, global observations of thermospheric composition and density profiles are needed.…”
Section: Introductionmentioning
confidence: 99%